-5(3x+2)=-3(x+2)

Simple and best practice solution for -5(3x+2)=-3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(3x+2)=-3(x+2) equation:


Simplifying
-5(3x + 2) = -3(x + 2)

Reorder the terms:
-5(2 + 3x) = -3(x + 2)
(2 * -5 + 3x * -5) = -3(x + 2)
(-10 + -15x) = -3(x + 2)

Reorder the terms:
-10 + -15x = -3(2 + x)
-10 + -15x = (2 * -3 + x * -3)
-10 + -15x = (-6 + -3x)

Solving
-10 + -15x = -6 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-10 + -15x + 3x = -6 + -3x + 3x

Combine like terms: -15x + 3x = -12x
-10 + -12x = -6 + -3x + 3x

Combine like terms: -3x + 3x = 0
-10 + -12x = -6 + 0
-10 + -12x = -6

Add '10' to each side of the equation.
-10 + 10 + -12x = -6 + 10

Combine like terms: -10 + 10 = 0
0 + -12x = -6 + 10
-12x = -6 + 10

Combine like terms: -6 + 10 = 4
-12x = 4

Divide each side by '-12'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| -4y-28=12 | | -3(-5x+9)=48 | | 9-=25 | | -2(-5-6x)=-14 | | 3(-5+6x)=-15 | | -17-9y=0 | | 6(-6-2x)=96 | | -5(7x+7)=-175 | | 5(2+3x)=-140 | | 3+1=n+3 | | 3(1x+4)=6 | | 4(7x+1)=200 | | -14-12x+30=28 | | 2m-3(5m-7)= | | 2(5x-2)=56 | | 3A-c+2a-3c= | | 7h-15=55 | | y^2+3y-7=6y+3 | | 3p+8-3(p+4)=1 | | 45.00(15+x)=1935.00 | | f(b)= | | 8x-x=10+1 | | 3x-2(4)= | | f(x)=x^3+4x^2+9x+10 | | 9x=5(2x-1) | | Y=3.5x+1 | | 8x+1=10-x | | 4x+5xy=18 | | x^2+2z-35=0 | | 1-x=3x+29 | | y^2-3y-14=0 | | 7x^3-50x=0 |

Equations solver categories